Developing the European Villages in the Republic of Moldova taken into account the Digital Economy Society Index (DESI) - Anatolii BABIN; Tatiana COLESNICOVA; Sergiu TUTUNARU (Smart Cities and Regional Development Journal, 2023)
The digital competitiveness of regions of EU member states is measured by the Digital Economy and Society Index (DESI), a composite index summarizing the progress made in connectivity, digital skills, internet use by citizens, digital integration of enterprises, farms and digital public services, while at the local government level there is currently no single indicator measured on a regular basis. Based on recent international and national researches, it can be concluded that with the development of digital technology, a significant increase in services and solutions available to citizens digitally is expected. Recent positive experiences of EU member states, which have been analyzed in previous research papers, show that the creation of jobs in agricol sectors in rural areas contributes to increasing household incomes. The objective of our study is to analyze and implement the methods and data sources for calculating DESI indicators at the level of local administrative units in the Republic of Moldova, in the context of the National Program for the European Village, launched in spring 2022. The results of the study will be the development of recommendations for local administrations on the use of the DESI index to coordinate the European evaluation parameters. The value of this work is in reinforcing activities for localisation of smart infrastructure and spatial data taking in consideration the DESI index and innovative products of the national Innovation Centres in innovative economics, stimulating investments in the creation of Smart Villages.